MODULATION OF GABA RELEASE FROM THE THALAMIC RETICULAR NUCLEUS BY COCAINE AND CAFFEINE: ROLE OF SEROTONIN RECEPTORS - Goitia, Belén (J Neurochem, 2015)
Serotonin receptors are targets of drug therapies for a variety of neuropsychiatric and neurodegenerative disorders. Cocaine inhibits the re-uptake of serotonin (5-HT), dopamine, and noradrenaline while caffeine blocks adenosine receptors and opens ryanodine receptors in the endoplasmic reticulum. We studied how 5-HT and adenosine affected spontaneous GABAergic transmission from thalamic reticular nucleus (TRN). We combined whole-cell patch clamp recordings of miniature inhibitory post-synaptic currents (mIPSCs) in ventrobasal (VB) thalamic neurons during local (puff) application of 5-HT in wild type (WT) or knockout mice lacking 5-HT(2A) receptors (5-HT(2A) −/−). Inhibition of mIPSCs frequency by low (10 μM) and high (100 μM) 5-HT concentrations was observed in VB neurons from 5-HT(2A)−/− mice. In WT mice, only 100 μM 5-HT significantly reduced mIPSCs frequency. In 5-HT(2A)−/− mice, NAN-190, a specific 5-HT(1A) antagonist, prevented the 100 μM 5-HT inhibition while blocking H-currents that prolonged inhibition during post-puff periods. The inhibitory effects of 100 μM 5-HT were enhanced in cocaine binge-treated 5-HT(2A) −/−. Caffeine binge treatment did not affect 5-HT-mediated inhibition. Our findings suggest that both 5-HT(1A) and 5-HT(2A) receptors are present in presynaptic TRN terminals. Serotonergic-mediated inhibition of GABA release could underlie aberrant thalamocortical physiology described after repetitive consumption of cocaine.